Regional enlarged observability of fractional differential equations with Riemann—Liouville time derivatives - Zouiten, Hayat (2019)
We introduce the concept of regional enlarged observability for fractional evolution differential equations involving Riemann-Liouville derivatives. The Hilbert Uniqueness Method (HUM) is used to reconstruct the initial state between two prescribed functions, in an interested subregion of the whole domain, without the knowledge of the state